Color polymorphism of a shell and the aminotranferase activity in Mytilus galloprovincialis Lam. tissues - Kulikova, A.D.; Andreenko, T. I.; Soldatov, A.A. (Reports of the National Academy of Sciences of Ukraine, 2014)
Using the method of digital photo processing, four color groups of Mytilus galloprovincialis are determined: black, intermediate, dark and light brown. The activities of alanine and aspartate aminotransferases taking part in processes of anaerobic metabolism between groups are significantly different. The highest divergence (1.5–2.8 times) was observed between the edge groups with black and light brown shell color. This is apparently related to mussel’s adaptation to environmental conditions of rocky shores and seabed ecotops.